2016
DOI: 10.22226/2410-3535-2016-4-338-342
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal grain growth in YBa2Cu3O7−x high-Tc superconducting ceramics during high-temperature deformation

Abstract: Bimodal microstructure is formed in high-T c superconducting ceramics YBa 2 Cu 3 O 7−x deformed by torsion under pressure at T d = 1008°C. The appearance of second peak on the grain length distribution is associated with formation of abnormally coarse grains with length up to l = 300-500 μm. Cooling rate has almost no effect on the density of abnormal grains n and l, indicating that such grains are formed during deformation. The l value increases monotonically with increasing twist angle α, while n increases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, the microstructure of the 3D-printed ceramics indicated that TiO 2 excess in the initial BT powder was necessary but not sufficient for AG growth (Figure 10c). Local strains occurring on green body pressing could be assumed as a supplementary factor for the formation of AG [29][30][31]. In a case of 3D printing, the powder particles underwent a slow packing process during the debinding, without any external mechanical pressure.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…However, the microstructure of the 3D-printed ceramics indicated that TiO 2 excess in the initial BT powder was necessary but not sufficient for AG growth (Figure 10c). Local strains occurring on green body pressing could be assumed as a supplementary factor for the formation of AG [29][30][31]. In a case of 3D printing, the powder particles underwent a slow packing process during the debinding, without any external mechanical pressure.…”
Section: Materials Characterizationmentioning
confidence: 99%